Inkjet printing of ZTO and AlOx solution combustion inks for electronic devices production - Moreira, Pedro Gabriel (2022)
Solution processed amorphous metal oxides have been showing competitive electronic performance to the ones produced by vacuum-based techniques, reducing the associated cost. These metal oxides are compatible with a variety of upscaling printing techniques, however, is crucial the optimization of the printing process to obtain stable, reproducible, and high-performance devices. Furthermore, it is important to find alternatives to some of the elements often used (gallium and indium) due to their toxicity and scarcity as well as finding safer solvents to those used in industry. The compatibility with inkjet printing (IJP) of solution processed aluminum oxide (AlOx) (2-methoxyethanol as solvent) and zinc tin oxide (ZTO) using different solvents: ethanol, ethanol (50%).H2O (50%), 1-methoxy-2-propanol (1-MP) and 2 methoxyethanol (2-ME) was performed. Spin-coated ZTO thin film transistors (TFTs) based on ethanol did not show promising results. Spin-coated devices using 1-MP as solvent had decent performance with IOn/IOff ratios of 105 and low subthreshold swing (SS) of 0.66 V.dec-1, however the ink is not compatible with inkjet printing. IJP of 2-ME based ZTO and AlOx thin films was optimized by changing the ultraviolet pre-treatment time, the drops per inch (DPIs), post annealing time, printing speed and number of layers. IJP printed metal-insulator-semiconductor (MIS) capacitors with AlOx based on 2-ME as solvents were printed with one- and two-layers showing breakdown voltages above 1 MV.cm-1. Lastly IJP ZTO/AlOx TFTs based on 2-ME as solvent were achieved with competitive performance showing a mobility of 2.2 cm2.V-1.s-1, a SS of 0.49 V.dec-1 and a IOn/IOff current ratio of 103 on the best devices. The results are the first fully IJP TFTs at CENIMAT/CEMOP and are in accordance with the values typically reported in literature for solution processed ZTO and AlOx, with performance matching devices produced by spin-coating.